2006
DOI: 10.1002/bjs.5224
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the small intestine as a cause of the increased inflammatory response after open compared with laparoscopic surgery

Abstract: Manual handling of organs during gastrectomy is an important contributor to the molecular and humoral inflammatory response to surgery, supporting the use of minimally invasive techniques in gastrointestinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 28 publications
4
55
0
8
Order By: Relevance
“…Based on the results of this study, the LC group had better scores in many aspects. Hiki et al performed one QOL measurement after six weeks on patients that had undergone open and laparoscopic colorectal surgeries and reported a difference in four of eight aspects of the SF-36 including: "pain", "social functioning", "role limitations due to physical health" and "role limitations due to emotional problems" (16). This result was consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the results of this study, the LC group had better scores in many aspects. Hiki et al performed one QOL measurement after six weeks on patients that had undergone open and laparoscopic colorectal surgeries and reported a difference in four of eight aspects of the SF-36 including: "pain", "social functioning", "role limitations due to physical health" and "role limitations due to emotional problems" (16). This result was consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Another potential long-term advantage of LIR over CIR is a reduced formation of intra-abdominal adhesions. Although some studies of which most are experimental have shown a reduction of intra-abdominal adhesion formation after laparoscopic surgery, its clinical relevance remains to be determined[ 42, 43]. Finally, LIR might be associated with a decreased number of incisional hernias.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines also define laparoscopy-assisted surgery as a treatment of clinical stage IB cancer. The quality of laparoscopic surgery is reported not to be worse than conventional open laparotomy surgery, and the surgical invasiveness is reported to be less in laparoscopy-assisted surgery [12, 13]. A new issue in the laparoscopic surgery is the education of younger surgeons.…”
Section: Surgical Treatmentmentioning
confidence: 99%